2017
DOI: 10.1101/171082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide characterization of Phytophthora infestans metabolism: a systems biology approach

Abstract: 22Genome-scale metabolic models (GEMs) provide a functional view of the complex 23 network of biochemical reactions in the living cell. Initially mainly applied to reconstruct 24 the metabolism of model organisms, the availability of increasingly sophisticated 25 reconstruction methods and more extensive biochemical databases now make it possible 26 to reconstruct GEMs for less characterized organisms as well, and have the potential to 27 unravel the metabolism in pathogen-host systems. Here we present a GEM f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…This highlights that similar evolutionary forces due to the adaptation to similar lifestyles will lead to convergent patterns (Kemen et al 2011; Sharma et al 2015b). In line with previous studies, we found that the metabolic networks of obligate pathogens are generally smaller (Rodenburg et al 2018; Spanu 2012) and lack enzyme-encoding genes for reactions in various metabolic pathways (Judelson 2017; Kemen et al 2011; Sharma et al 2015a; Baxter et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This highlights that similar evolutionary forces due to the adaptation to similar lifestyles will lead to convergent patterns (Kemen et al 2011; Sharma et al 2015b). In line with previous studies, we found that the metabolic networks of obligate pathogens are generally smaller (Rodenburg et al 2018; Spanu 2012) and lack enzyme-encoding genes for reactions in various metabolic pathways (Judelson 2017; Kemen et al 2011; Sharma et al 2015a; Baxter et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This example nicely demonstrates how one can analyze transcriptome data in a system-wide context. In concordance with related transcriptome studies (Abrahamian et al, 2016;Ah-Fong et al, 2017a), the transcriptome-based submodels reflected reduced metabolic activity in the sporangial stages of P. infestans, and nutritional changes in the transition from a biotrophic to a necrotrophic stage of infection on tomato leaves (Rodenburg et al, 2017(Rodenburg et al, , 2019. Importantly, because these transcriptomic changes were analyzed in the context of a GEM, results were subject to the imposed model constraints (steady-state, reaction thermodynamics) and thereby to the topology of the metabolic network (Hyduke et al, 2013).…”
Section: Modeling Phytophthora Infestans Metabolism To Predict Pathogen-host Interactionsmentioning
confidence: 79%
“…Metabolic enzymes are located in various organelles, and hence, specific metabolic processes take place in different parts of the cell. In the reconstructed P. infestans models, this compartmentalization was taken into account to represent the spatial distribution of metabolic pathways in different subcellular compartments (Rodenburg et al, 2017(Rodenburg et al, , 2019. The transporters and channels responsible for transfer of metabolic substrates across membranes were modeled by integrating transport reactions (Thiele and Palsson, 2010).…”
Section: Modeling Phytophthora Infestans Metabolism To Predict Pathogen-host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of P. belbahrii was recently sequenced and annotated; a little over 9000 protein-coding genes were identified (THINES et al 2020). The genomic data of P. belbahrii and other downy mildew pathogens indicate that their metabolic networks were generally smaller than oomycetes that are hemibiotrophs or necrotrophs (SPANU 2012;RODENBURG et al 2018).…”
Section: Introductionmentioning
confidence: 99%